2012
DOI: 10.1186/1750-9378-7-30
|View full text |Cite
|
Sign up to set email alerts
|

Consistent condom use increases spontaneous regression in high-risk non-HPV16 but not in HPV16 CIN2-3 lesions, a prospective population-based cohort study

Abstract: BackgroundThe major cause of cervical intraepithelial neoplasia (CIN) is persistent infection with human papillomavirus (HPV). Most CIN grade 2 and 3 lesions are treated with cone excision, although a substantial proportion (6-50%) of CIN2-3 lesions will regresses spontaneously. Predictors for regression of CIN2-3 are desirable in order to reduce this overtreatment.MethodsIn this prospective cohort study, 145 consecutive women with first-time onset CIN2-3 in colposcopy-directed biopsies and standardized biopsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 250 potentially eligible studies; 43 publications met the inclusion criteria (fig 1),6222324252627282930313233343536373839404142434445464748495051525354555657585960616263 but seven were duplicate reports of the same data 27283140505254. Of the 36 eligible studies (total of 3160 women), seven (19%) were randomised trials with suitable data in the non-experimental arm,22253339455762 16 (44%) were prospective cohort studies,6263032343536373841435155566063 and 13 (36%) were retrospective cohort studies23242942444647484953585961 (see supplementary table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported in 10 articles met the inclusion criteria. 817 For one study, we tabulated the results from the first of three published articles; all three reported the same endpoint with marginally different inclusion criteria. 15…”
Section: Resultsmentioning
confidence: 99%
“…At baseline, Munk et al. 1517 asked 162 women with histologically-confirmed CIN2/3 to continue using their usual form of contraception, and to return for colposcopy two months, and again about three to six months after the baseline. Condom use was determined from interviews at baseline and final visits.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to HPV16, which is the most common genotype [ 25 ], other genotypes were also involved in both single infection or co-infection with HPV16. The prevalence pattern for specific genotypes in men is still unclear [ 26 ].…”
Section: Discussionmentioning
confidence: 99%